WHEN IS POSTCOMMUNISM OVER? - RomanyukО. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
In this article, the problem of postcommunism time limits is considered. The author, treating postcommunism as a transition period from the left-totalitarian model of social organization to a new one concludes that it is over in those countries where the communist regimes collapsed at the turn of 1980-1990 years. Although various postcommunist countries have acquired different parameters of their political, economic, socio-cultural systems, a new noncommunist quality of social relations hаs already established itself.